Stand-Alone Conclusion Section in Open-Access Research Articles: Organizational Structure - Budsaba Kanoksilapatham (National Research University Higher School of Economics, 2023)
Background: Research articles (RAs) have been highlighted as one of the most essential channels for academicians to disseminate knowledge. Typically, RAs consist of a nomenclature of the four sections of introduction, methods, results, and discussion, commonly known as IMRD, with each section governed by an organizational structure determined by genre analysis. However, due to the increasing prevalence of the stand-alone conclusion section in recent years and the expansion of open-access journals, understanding how this conclusion section is constructed can benefit scholars in an academic endeavor. Methods: This study aims to identify the organizational structure of the stand-alone conclusion section in open-access journals. An original dataset of 55 open-access journal RAs from four major academic disciplines honored as "Articles of the Year 2021" was analyzed. Only the RAs with stand-alone conclusions within a calculated word range were selected, yielding a final dataset of 25 comparable conclusion sections. Then, anchored on genre analysis, the compiled dataset was analyzed quantitively and qualitatively. Results: Based on the genre analysis conducted, a set of three moves and their pertaining steps were identified, forming various organizational patterns but one compelling one. Furthermore, the full-fledged two-layer rhetorical structure of the section depicting the frequencies of occurrence of individual moves and steps is quite revealing, highlighting the crucial significance of restating the findings generated from the study being reported. The results demonstrate not only how established this section is but also how it is currently structured, performing its critical function of concluding RAs. Conclusion: This study has provided insights into integrating analytical elements to successfully stage persuasive arguments in the conclusion section, a skill that needs to be inculcated in novice or early-career researchers and seasoned researchers alike.